Advancing educational quality: an online review analysis of stakeholder perceptions in bali international schools - Noerhartati, Endang; Handani, Narariya Dita; Dhaneswara, Nindya (Jurnal Ilmiah Pendidikan Dasar, 2024)
This study used word frequency and co-occurrence network analysis using KH Coder 3.0 to evaluate perceptions of international schools in Bali, as reflected in 614 online reviews. The analysis, which yielded an average satisfaction rating of 4.4 out of 5, identified school as the most common term and demonstrated its significance in the review. Frequent mention of children, students, teachers, as well as emotionally resonant terms such as amazing and nature, highlight society's emphasis on educational quality, student-teacher relationships, and the ethos of the school environment. This network of co-occurrences further reveals the importance of community, curriculum, and the integration of Balinese cultural and natural elements into the educational experience. This research aims to fill this gap by examining how online reviews of international schools in Bali influence their reputation among the expatriate community and influence parents' choices. The result of this research is an analysis of customer responses to international schools in Bali, which were assessed quantitatively and qualitatively in this research, providing strong evidence of the high regard for these institutions. An average rating of 4.4 out of 5 stars, based on a large number of reviews, indicates strong satisfaction among parents and students with the educational services provided. Green School's outstanding performance, in terms of review volume, is an exemplary example of educational excellence that can serve as a benchmark for other schools. These insights, gained from the application of a robust methodology using KH Coder 3.0, not only confirm the current strength of educational institutions but also pave the way for targeted strategies to address potential growth.